Handbook of sustainable polymers : structure and chemistry - Thakur, Vijay Kumar, 1981-; Thakur, Manju Kumari (CRC Press : Pan Stanford Publishing, 2016)
Sustainable polymers play an indispensable role in the emergence of green materials, and the 21st century is an era of sustainable polymeric materials. Sustainable polymer--based materials have attracted considerable interest because of the energy crisis and ecological concerns as well as the potential to substitute certain petroleum-derived materials. This book covers the fundamentals of sustainable polymers and presents guidelines in a logical and clear manner for students and researchers to follow. It is a milestone that will help accelerate the progress and advancement in the field of sustainable polymers. The text explores the structure and chemistry of various sustainable polymers, such as cellulose, hemicellulose, lignin, chitosan, starch, guar gum, pectin, and protein, for the possible development of green sustainable materials.
Keywords: Polymers -- Handbooks, manuals, etc.; elektronické knihy; electronic books